STUDI SIFAT OPTIK BERDASARKAN PREKURSOR DALAM SINTESIS ZnO - Viza Novia Putri; Iwantono Iwantono; Puji Nurrahmawati; Nashiha Chalvi Syahra (Komunikasi Fisika Indonesia, 2023)
ZnO is a semiconductor material that can be applied for solar cells, biosensors, and electronics. In this study, the synthesis of ZnO was carried out using two precursors, namely zinc acetate dihydrate (ZAD) and zinc nitrate hexahydrate (ZNH). Synthesis of ZnO determine the optical properties based on the precursors. The synthesis of ZnO by hydrothermal method. The results of ZnO were analyzed using UV-Vis spectroscopy characterization. UV-Vis spectroscopy characterization determine for the absorbance and transmittance of the samples. The wavelength range was 200 – 800 nm. The absorbance spectrum shows strong absorption occurs at UV wavelengths. That are effectively applied to solar cells. The highest absorbance was obtained by the ZAD precursor. The transmittance for the ZAD precursor exceeded 8.8% and ZNH precursor it exceeded 19.7% at visible light wavelengths. The band gap energy of ZnO with ZAD precursor and ZNH precursor are 2.85 eV and 2.87 eV. Furthermore, other optical properties have been calculated from absorbance measurements such as the urbach energy.